Physiology, cell dynamics of small intestinal mucosa, and performance of broiler chickens under heat stress: a review - Marchini, Cristiane FP; Café, Marcos B; Araújo, Eugênio G; Nascimento, Mara RBM (Revista Colombiana de Ciencias Pecuarias, 2016)
High room temperature reduces production efficiency of broiler chickens. Different factors contribute to this situation: fast growth, physiological variations, and changes in the small intestine mucosa. This review aims to define the concept of heat stress and its effects on several physiological aspects related to the development of the small intestine mucosa and the performance of broiler chickens. Heat stress triggers a corticosteroid increase and a circulating triiodothyronine hormone (T3) reduction, increases respiratory frequency, which triggers respiratory alkalosis, diminishes food intake, and leads to changes in the cellular dynamics of the small intestine mucosa. These changes depend on animal genotype, intensity, and duration of the stressor. Acute heat stress leads to a reduction in enterocyte proliferation and also to a decrease in crypt depth, without affecting villus height or villus/crypt ratio. On the other hand, chronic stress diminishes villus height and jejunum weight. These changes affect the capacity of broilers to digest and absorb the nutrients required for maintenance and production.